(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
Identification of an individual is one of the main objectives carried out in day to day medico legal work. Fixing the individuality of a person requires different characteristic features specific to the person. Stature of a person is one among the many features helping in the identification of a person. In the past, many studies have been conducted showing the positive correlation between stature of an individual and other anthropometric measurement. Aim of the present study is to find a relation between height and foot length and derive a regression equation that can be helpful to estimate the height of a person from the foot length. This study was conducted on 100 male students. The mean left foot length and right foot length were 26.15 and 26.25 respectively. Height of the subjects varied from 158 cm to 185 cm. A significant correlation was found between the foot length and the height.